Endurance and Respiratory Training, an Approach to Delay the Symptomatic Progression in Multiple Sclerosis - A Case Report (Indian Journal of Forensic Medicine & Toxicology, 2021)
Multiple sclerosis (MS) is an autoimmune disease which is inflammatory in nature and shows gliosis anddemyelination which lead to acute and chronic symptoms impairing the quality of life due to disability.Presence of immune-mediated response in Central Nervous System leads to the above presentation. MSis the most common condition of CNS which causes disability. Treatment of Multiple Sclerosis consistsof treating the exacerbations along with slowing the disease process and including symptomatic therapies.The most invalidating symptom in people with MS is Fatigue. This case reports shows the effectiveness ofendurance and respiratory training towards the delaying the progression of symptoms in MS.
Keywords: Multiple Sclerosis, Endurance Training, Respiratory Training, Neurological Condition